A ECONOMIA PARALELA E A CORRUPÇÃO NA UE-28: Relação, Causas e Consequências - Ângela Cristina Pereira Marques (2017)
The relationship between Shadow Economy and Corruption is not clear. These can be complementary or substitute of each other, and may exhibit a positive or negative relation. This work aims to explore the relation between Shadow Economy and Corruption using panel data for the 28 countries of the European Union during the period from 2000 to 2014. This work also intends to contribute to a better understanding of the causes of Shadow Economy and Corruption and enumerate some of the most detrimental consequences of the two phenomena. Using a simple model, where OLS regressions with fixed effects and random effects are used, two aspects of the literature are combined. On one hand the impact of Corruption and other explanatory variables in the Shadow Economy is studied, on the other hand, the influence of the Shadow Economy and other control variables on Corruption is analyzed. The obtained results show that there is evidence that Shadow Economy and Corruption are complementary. This relationship is most evident when Corruption explains the Shadow Economy than when Shadow Economy explains Corruption. That is, we can conclude that Corruption influences more the Shadow Economy, than the Shadow Economy influences Corruption. Of the explanatory variables selected for the study, the ones that have most weight in the explanation of the Shadow Economy are the Business Regulation Load, the Transfers and Subsidies and the Government Consumption. In turn, the variables that most affect Corruption are Government Effectiveness and the Rule of Law.